Ideology through modality - Badran, Dany (2002)
This study is broadly concerned with the analysis of ideology in discourse. More specifically, it investigates the role modality plays in reflecting underlying ideologies as well as ideological inconsistencies in three practical analyses of discourse. Achieving these objectives is, I argue, dependent on a view of discourse which is not only functional but also pragmatic. The functional aspect of this view reflects the broad objectives of functional linguistics: i.e. relating linguistic structures to social structures. The pragmatic aspect reflects an emphasis on the need not to exclude 'the reader' from the process of interpretation. Whereas previous studies have either entirely neglected or presented an unsatisfactory account of the reader, the proposed functional-pragmatic approach to discourse analysis resolves this issue by allowing a systematic variance in interpretation. This is done in the light of a systematic account of modality which helps present a realistic and practical consideration of the role of the reader in approaching discourse analysis. Again, in line with a functional and pragmatic view of discourse, the argument put forward in this study is that all 'types' of discourse can be approached in a similar manner for critical analysis. Consequently, practical analyses of ideology through modality in three instances of discourse: literary texts, political texts and scientific texts are presented. The overall aim is to show how a systematic, functional and pragmatic analysis of modality is adequate in critically analysing the ideologies present in all texts.